Hybrid electromagnetic suspension for high-speed vacuum transport - Nikolay Grebennikov; Alexander Kireev; Nikolay Kozhemyaka; Gennady Kononov (Institute of Advanced Engineering and Science, 2019)
The given paper presents a hybrid electromagnetic suspension designed for high-speed vacuum transport, where the main levitation force is generated by permanent magnets, while the electromagnet controls the air gap. The computer model is designed by means of MATLAB/Simulink software package, which allows us to simulate the dynamic operational modes of the system. The calculated studies are carried out when the vehicle accelerating to 1000 km/h with account of track irregularities. Permanent magnets incorporated in the system of electromagnetic suspension make it possible to reduce the energy consumption needed for levitation force generation.